Book Review of Petr Pervyi i osvoenie severa Tikhogo okeana [Peter the Great and the Development of the North Pacific] by A.Yu. Petrov. Ryazan: Ryazanskii gosudarstvennyi universitet imeni S.A. Yesenina Publ., 2022. 280 p. (in Russian) - Vardan E. Baghdasaryan; Sergey I. Resnyansky (RUDN Journal of Russian History, 2023)
-